Analysing and Prioritizing the Antecedents of Customer Shopping Experience Using Analytical Hierarchy Process (AHP) Modelling. (January 2018) - Singh, Priyanka; Singh, Maninder
The aim of this study is to analyse and prioritize the antecedents of customer shopping experience to enhance the understanding of marketers about what their consumers really want. The construct of customer shopping experience in the consumer behaviour theory is a well acclaimed one and has been studied in several contexts with varied perspectives; however, the researchers seldom noticed any endeavour to prioritize the antecedents of the shopping experience from the experts' viewpoint. The present study endeavours to utilize analytical hierarchy process (AHP) modelling to find the degree of importance that customers attach to different criteria of the three key precursors of shopping experience, that is, the store environment, the social environment and the purchase motives with their underlying sub-criteria. The results of the study evidently propagate social environment as the most important criterion followed by store environment and purchase motives. This ranking is not just an ordinary exposition of placing one before another, but it expounds that the consumer is much concerned about the environment while making a buying decision. The key sub-criterion of social environment is customer interaction, which means that the customer is more concerned about the social interactions that have the potential to influence their psychology when they shop with their family or peer group. These results have several interestingly explorable implications for both retailers as well as marketers.